Effect of Heat and Moisture Exchange Filter on the Dead Space Ventilation in a Pediatric Patient - Bhagwat, Mrunmayee; Surve, Rohini M.; Patwardhan, Prathamesh (Journal of Neuroanaesthesiology and Critical Care, 2021)
The use of heat and moisture exchange filter (HMEF) has become a routine standard of care in general anesthesia (GA), more so, during the current COVID-19 pandemic times. However its routine use, especially in pediatric patients, has several issues. We report a case of increased dead space ventilation in a pediatric patient due to the presence of HMEF. Hypercapnia and its cause was instantly diagnosed with two capnography sampling lines placed at two ends of the HMEF.
Keywords: heat and moisture exchange filter; hypercapnia; pediatric anesthesia